The Rehabilitation Of Abandoned Housing Project: An Overview And Case Study Of The Process And The Problems Faced - Lee, Din Wee (Universiti Sains Malaysia, 2007)
Abandoned housing project is a serious problem in Malaysia. The abandonment of houses has brought huge impact to our economy as well as to those suffered purchaser as they had already paid for house loan but their house is uncompleted. Subsequently, the incident will bring mentally influence and blow their confidence upon the housing scheme in Malaysia.